Cutaneous Asthenia in a Domestic Cat (Felis silvestris catus) - Andrade, Ana Cláudia de Souza; Rey, Laisa Marina Rosa; Santos, Isabela Carvalho dos; Charnovski, Sarah Gabriella Delallo; Czornobai, Diogo; Silva, Lariane Souza; Sabadin, Jéssica Crespi; Gonçalves, Daniela Dib (Acta Scientiae Veterinariae, 2021)
Background: Cutaneous asthenia or Ehlers-Danlos syndrome is an inherited and rare disease. This infirmity is from an autosomal mutation that influences the collagen synthesis of the carrier. Thus, its skeleton, formed of fibers, is structurally defective. The disease is characterized by hyperelasticity and skin fragility, leading to lesions throughout the skin. The lesions may manifest in specific places or in a generalized way, being more frequent in the limbs, neck, and back. This disease does not have a specific treatment, only management care to avoid new traumas. Case: A 3-year-old male castrated, no defined race cat, was attended at one veterinary clinic with a history of intense itching. The rapid tests for feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) were negative. On physical examination, infestation by fleas, lesions all over the body, and skin hyperelasticity were observed. Topical treatment for ectoparasites as well as for body wounds was established. After the treatment, he returned without itching, but with the complaints of new lesions that did not heal. The patient underwent a total shearing to facilitate the treatment of the skin, and then he underwent blood tests, biochemistry, hormonal tests, and ultrasound, which showed no suggestive changes for hyperadrenocorticism and diabetes mellitus. His clinical signs, besides not matching with these diseases, also did not indicate skin fragility due to his history of age and balanced diet. The confirmation of the cutaneous asthenia syndrome was acquired through biopsy of skin fragment, in which it was observed disarray of collagen fibers, hypertrophy, and fibroblast hyperplasia, together with the rate of extensibility of the skin where the value reached the mark of 27.5%. Throughout the hospitalization, it was noted the progression of the disease with the appearance of new lesions, where there was no bleeding and they appeared even with the patient wearing padded clothes. Its progression lasted one year until the patient's euthanasia. Discussion: For the disposal of diabetes mellitus and hyperadrenocorticism as causes of the appearance of lesions by the body in the patient, he was submitted to the suppression tests with dexamethasone, in which he presented normality, in the biochemical examination it was dosed with fructosamine and glucose. The fructosamine was in the reference value, but the glucose was slightly altered, this increase may have been a result of stress at the time of blood collection. In addition to the patient not showing specific clinical signs such as polyphagia, polyuria, polydipsia, and weight loss, these are characteristic clinical signs of the disease. For the diagnosis of Ehlers-Danlos syndrome, histological examination, and calculation of the skin extensibility index were used, where the results obtained confirmed the suspicion. This genetic anomaly has no treatment, being progressive, so only environmental management is done to mitigate the appearance of the lesions and provide animal welfare. This case report contributes to aggregating the scientific literature in the area of veterinary medicine since skin asthenia is a rare disease and when its extent is total it becomes even more atypical. The availability of this article will provide a vision of palliative treatment for other cases, demonstrating the progressive nature of the lesions and the methods of diagnosis. Keywords: cat, collagen deficiency, ehlers-danlos syndrome, hyperelastic, skin.